2006
DOI: 10.1073/pnas.0600326103
|View full text |Cite
|
Sign up to set email alerts
|

CTCF binding at the H19 imprinting control region mediates maternally inherited higher-order chromatin conformation to restrict enhancer access to Igf2

Abstract: It is thought that the H19 imprinting control region (ICR) directs the silencing of the maternally inherited Igf2 allele through a CTCFdependent chromatin insulator. The ICR has been shown to interact physically with a silencer region in Igf2, differentially methylated region (DMR)1, but the role of CTCF in this chromatin loop and whether it restricts the physical access of distal enhancers to Igf2 is not known. We performed systematic chromosome conformation capture analyses in the Igf2͞H19 region over >160 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
420
3
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 481 publications
(445 citation statements)
references
References 43 publications
16
420
3
4
Order By: Relevance
“…A mouse fibroblast cell line (MBW2) derived by breeding M. spretus males with C57BL/c females (6) was used to study the allelic interactions with CTCF. We first examined whether CTCF interacts directly with the Igf2 promoters by 3C methodology (17). CTCFbound DNA in the ICR (EcoRI sites 5 and 6) interacted with the DNA near the imprinted promoters primarily on the maternal allele (EcoRI sites 2 and 3, lanes 3 to 6, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A mouse fibroblast cell line (MBW2) derived by breeding M. spretus males with C57BL/c females (6) was used to study the allelic interactions with CTCF. We first examined whether CTCF interacts directly with the Igf2 promoters by 3C methodology (17). CTCFbound DNA in the ICR (EcoRI sites 5 and 6) interacted with the DNA near the imprinted promoters primarily on the maternal allele (EcoRI sites 2 and 3, lanes 3 to 6, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…When this ICR is deleted (35) or mutated (32, 34), the maternal Igf2 allele is expressed, leading to biallelic expression. In addition, CTCF has recently been shown to act as a tethering protein, serving as a molecular glue to secure long-range intrachromosomal (17) and interchromosomal (18) interactions.By chromosome configuration capture (3C) methodology, it has been shown that CTCF participates in the formation of a long-range chromosomal loop to the upstream Igf2 DMRs when it is bound to the maternal ICR (17,42,21). This model suggests that CTCF may not only function as a physical insulator but also actively participate in the regulation of the imprinted Igf2 allele.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 In the mouse genome, the imprinted H19/Igf2 locus in particular has yielded several insights into chromosomal organization mediated by CTCF. Not only has intrachromosomal association of elements within the locus been detected, 17,18 but interchromosomal association between the locus and elements on different chromosomes has also been observed. 19,20 Loss of a CTCFmediated loop is sometimes also correlated with reduced transcription.…”
Section: Introductionmentioning
confidence: 99%